The outlaws - Griffin, W. E. B. frey50; Butterworth, William E. (New York : G.P. Putnam's Sons, 2010)
Charlie Castillo's secret unit has been disbanded, but that doesn't mean he's out of business. A FedEx package arrives, bearing photos of barrels containing some of the most dangerous biohazard materials on Earth, all of which were supposed to have been destroyed during a raid on a secret Russian factory in the Congo. Who has them, and what do they want? Castillo has a feeling he's not going to like the answers.
Map on lining papers.
Keywords: United States. -- Army. -- Delta Force; Undercover operations; Suspense fiction; Suspense fiction; Suspense fiction